Rapid screening of mycotoxins in liquid milk and milk powder by automated size-exclusion SPE-UPLC–MS/MS and quantification of matrix effects over the whole chromatographic run. (15th April 2015) - Wang, Xiupin; Li, Peiwu
Highlights: A pretreatment-free size-exclusion solid phase extraction (SPE)-UPLC–MS/MS protocol. A mixed macropore-silica gel cartridge as a size-exclusion SPE column. Permanent postcolumn infusion of standard samples was used to quantify matrix effect. Matrix-matched calibration could compensate for strong matrix enhancement effects. Abstract: An automated, size-exclusion solid phase extraction (SPE)-UPLC–MS/MS protocol without pre-treatment of samples was developed to screen for four mycotoxins (OTA, ZEN, AFB1, and AFM1 ) in liquid milk and milk powder. Firstly, a mixed macropore-silica gel cartridge was established as a size-exclusion SPE column. The proposed methodology could be a candidate in green analytical chemistry because it saves on manpower and organic solvent. Permanent post-column infusion of mycotoxin standards was used to quantify matrix effects throughout the chromatographic run. Matrix-matched calibration could effectively compensate for matrix effects, which may be caused by liquid milk or milk powder matrix. Recovery of the four mycotoxins in fortified liquid milk was in the range 89–120% and RSD 2–9%. The LOD for the four mycotoxins in liquid milk and milk powder were 0.05–2 ng L −1 and 0.25–10 ng kg −1, respectively. The LOQ for the four mycotoxins in liquid milk and milk powder were 0.1–5 ng L −1 and 0.5–25 ng kg −1, respectively.